Digitalisasi Pelayanan Publik Pada Desa Salo Timur Dengan Sistem Informasi Berbasis Website - Antoni Pribadi; Andri Nofiar; Fenty Kurnia Oktorina; Fina Nasari; Fitri Fitri; Muhammad Ridwan; Slamet Triyanto; Muhammad Jazman (ABDIMAS TERAPAN : Jurnal Pengabdian Kepada Masyarakat Terapan, 2023)
The process of administering East Salo Village administration, including general administration, population administration, development administration. The problem faced by partners, namely conveying information about Village potential, population, Village activity agenda, Village Budget carried out by Village officials to the local community, is by conveying socialization directly at the East Salo Village office or making banners outside the Village office regarding the Village Expenditure Budget ( APBDes). The obstacles faced by the community if they want to get information quickly, are often hampered by the working hours of village officials and during the socialization carried out by East Salo Village officials, not all people attend the socialization activities. Coupled with the lack of understanding of village officials regarding information technology, this means that services to the community are not optimal. The solution offered is by creating an information system based on the East Salo Village website and providing training to East Salo Village officials on the use of the information system created.